Effect of Implementing a Free Delivery Service Policy on Women’s Utilization of Facility-Based Delivery in Central Ethiopia: An Interrupted Time Series Analysis - Ayalneh Demissie; Alemayehu Worku; Yemane Berhane (Journal of Pregnancy)
Background. Access to and utilization of facility delivery services is low in Ethiopia. The government of Ethiopia introduced a free delivery service policy in all public health facilities in 2013 to encourage mothers to deliver in health facilities. Examining the effect of this intervention on the utilization of delivery services is very important. Objective. In this study, we assessed the effect of provisions of free maternity care services on facility-based delivery service utilization in central Ethiopia. Methods. Data on 108 time points were collected on facility-based delivery service utilization (72 pre- and 36 postintervention) for a period of nine years from July 2007 to June 2016. Routine monthly data were extracted from the District Health Information System and verified using data from the delivery ward logbooks across the study facilities. An interrupted time-series analysis was conducted to assess the effect of the intervention. Results. The implementation of the free delivery services policy has significantly increased facility deliveries. During the study period, there was a statistically significant increase in the number of facility-based deliveries after the 24th and 36th months of intervention (p<0.05). Program effects on the use of public facilities for deliveries were persisted over a longer exposure period. Conclusion. The findings suggested that the provision of free delivery services at public health facilities increased facility delivery use. The improved utilization of facility delivery services was more marked over a longer exposure period. Policy-makers may consider mobilizing the communities aware of the program at its instigation.